From Lithium‐Metal toward Anode‐Free Solid‐State Batteries: Current Developments, Issues, and Challenges. (13th September 2021) - Heubner, Christian; Maletti, Sebastian; Auer, Henry; Hüttl, Juliane; Voigt, Karsten; Lohrberg, Oliver; Nikolowski, Kristian; Partsch, Mareike; Michaelis, Alexander
Abstract: The development of rechargeable batteries with high‐energy density is critical for future decarbonization of transportation. Anode‐free Li‐ion batteries, using a bare current collector at the anode side without any excess of Li, provide the highest volumetric energy density (> 1500 Wh L −1 ) among all possible cell configurations. Furthermore, elimination of the anode material coating reduces material consumption and greatly simplifies cell production, which in turn lowers costs. Although significant progress has been made recently by the application of modified current collectors, optimized cycling parameters and improved liquid electrolytes, insufficient efficiencies, and dendritic growth during lithium plating lead to poor cycle life of typically less than 100 cycles as well as safety issues. Alternatively, very recent studies have demonstrated anode‐free solid‐state batteries that combine the benefits of high energy anode‐free cell configuration and solid‐state systems with high safety, exceeding 1000 cycles. This review provides an overview of recent developments toward anode‐free solid‐state batteries and highlights the current issues and challenges in this nascent field. It is concluded that, although major challenges remain at the present, the lessons learned in the fields of liquid electrolytes and solid‐state lithium metal batteries can accelerate the development of anode‐free solid‐state batteries of practical relevance. Abstract : Recent developments in the field of anode‐free solid‐state batteries (AFSSB) are systematically reviewed, including energy density, cost, manufacturing, and recyclability. Lessons learned from liquid electrolyte systems are evaluated regarding the transfer to AFSSB. Current developments and major achievements are highlighted. Key challenges, including coulombic efficiency, interfacial issues, dendrite growth, and cell design, are summarized, emphasizing promising solution strategies.